Reliability analysis of dynamic systems : efficient probabilistic methods and aerospace applications - 312788 Wu, Bin (Amsterdam ; Boston : Elsevier, Academic Press is an imprint of Elsevier, 2013)
Includes bibliographical references (pages 191-197) and index